Philodryas chamissonis (Reptilia: Squamata: Colubridae) preys on the arboreal marsupial Dromiciops gliroides (Mammalia: Microbiotheria: Microbiotheriidae) - S. Muñoz-Leal; K. Ardiles; RA. Figueroa; D. González-Acuña (Brazilian Journal of Biology)
Philodryas chamissonis, the Chilean long-tailed snake, is a diurnal predator mainly of Liolaemus lizards, but also of amphibians, birds, rodents and juvenile rabbits. Dromiciops gliroides (Colocolo opossum) is an arboreal marsupial endemic of temperate rainforest of southern South America. Little information is available about this marsupial's biology and ecology. Here we report the predation of one Colocolo opossum by an adult female P. chamissonis in a mixed Nothofagus forest, composed mainly by N. dombeyi, N. glauca and N. alpina trees, in the "Huemules de Niblinto" National Reserve, Nevados de Chillán, Chile. Since these two species have different activity and habitat use patterns, we discuss how this encounter may have occurred. Although it could just have been an opportunistic event, this finding provides insights into the different components of food chains in forest ecosystems of Chile.